A Study of Some Ecological Parameters of Numerical diversity of Entomopathogenic Fungi in Soils of AboKawook and Saasa regionsIn Damascus Countryside (Damascus University Journal of agriculture sciences, 2025)
The diversity and seasonal abundance of Entomopathogenic fungi were investigated in soil samples collected from two localities, (AboKawook and Saasa) in Rural Damascus governorate, Syria, during 2020 – 2021. Soil samples from several agricultural orchard fields and they were taken to Biological Control Studies and Research Center (BCSRC) (Faculty of agriculture, Damascus).fungi species diversity was assessed using two indicators: species richness (S) and Shannon index (H).the results of this research revealed the presence of 17 species of entomopathogenic fungi, belonging to 11 genera Isolates from the genus Beauveria were the most frequent and abundant entomopathogenic species recovered, comprising 15.7% of the total number of isolates. in two localities,Diversity indices varied between two localities. The highest value was recorded at the locality Saasa (2.67), whereas the lowest was seen at the site AboKawook (2.49). The maximum similarity index (SQ( (0.87) was recorded between localities.
Keywords: Diversity; Richness; Entomopathogenic Fungi; species